Sinkretisme Agama dan Budaya dalam Tradisi Sesajen di Desa Prenduan - Aminullah Aminullah (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2017)
It is an obvious fact that culture and religion are often inseparable. For Muslims, some of cultures they live in are sometime not in line with their religion teachings. One of the examples is offering tradition. It is considered shirk for some of Islamic leaders. But then, it is still maintained by people in Prenduan, where the majority is Islamic believers. This shows that this tradition is a syncretic practice combining religious and culture. This research is aimed to investigate the syncretic process and value of offering tradition. Phenomenological approach is used in this study. Data are collected used interview, observation, and documentation which combined in the field notes and analyzed through data reduction, categorizing and making sense of the essential meanings of the phenomenon. The result shows that syncretic process in Prenduan was started from the old offeringtradition which was difficult to stop and the decrease of Prenduan people understanding of the tradition. So that, the Islamic leaders tried to modify the tradition, taking advantage of the limited understanding, by bringing Islamic teachings in people belief and their way of doing offering tradition. This study concludes that syncretic value of the tradition is in the way of doing and the belief of Prenduan people about the tradition.